MODEL PEMBERDAYAAN ASET WAKAF MELALUI CROWDFUNDING BAGI UMKM DI PROVINSI ACEH - Maesaroh, Siti; Kurnia, Tuti; Alhifni, Anas (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2024)
This research aims to determine the Aceh Province waqf asset empowerment model for MSMEs as a solution to overcome the problems and needs of MSMEs. This research method uses a descriptive qualitative method with a quantitative approach. The data analysis technique used is the Analytical Network Process (ANP) where data is collected through interviews and distributing questionnaires. The technique used in sampling was purposive sampling with a total sample of 30 MSMEs in Aceh Province. The results of this research show that the needs of MSMEs in Aceh Province are improving product quality at affordable prices, strategic business locations and business capital. The waqf asset empowerment model that can be a solution to the needs of MSMEs is the MSMEs Financing model which is a waqf asset empowerment model for MSMEs, where waqf assets are produced by utilizing funding through crowdfunding. Then, after the waqf assets produce benefits, MSMEs can receive benefits from the productive waqf assets in the form of capital loans with a qard-hasan agreement and facilitation of shops with cheap rental prices for MSMEs. Based on the needs of MSMEs, the waqf model is appropriate to help meet the needs of MSMEs